Respuesta :
Answer:
The function is
[tex]D(t) = 100 \times( \frac{40}{100} )^{t}[/tex]
Step-by-step explanation:
At t = 0 the difference is 100 degree celsius.
After one second the temperature difference will be [tex]100 - \frac{100\times60}{100}[/tex] = [tex]100(1 - \frac{60}{100} )[/tex]
After two second, the difference will be [tex]100(1 - \frac{60}{100} )(1 - \frac{60}{100} ) = 100(1 - \frac{60}{100} )^{2}[/tex]
Hence, it can be written that,
[tex]D(t) = 100 \times(1 - \frac{60}{100} )^{t}[/tex] = [tex]100 \times( \frac{40}{100} )^{t}[/tex]